A Tale of Two Cities: Exploring Factors Affecting Online Learning Equity - Bhattacharjee, Sunrita Dhar; Srivastava, Aarti; Chopra, Ekta; Sarkar, Sujata; Akhlaq, Muzammil; Upadhayay, Anjoo; Upadhayay, Prof Priyankar; Sule, Dr. Obehi (Indian Journal of Educational Technology, 2024)
The Covid pandemic has caused a significant shift in the education sector, pushing for rapid integration of technology in education worldwide. This has resulted in a move from traditional classroom learning to online and blended modes of learning, which is likely to continue. Though access to technology is crucial for driving innovation and equity in education, regional disparities have been widely pervasive, affecting overall educational governance at national, regional, and local levels. This paper delves into the problem of equity in online learning in Delhi and Varanasi, with a total of 2,563 responses and data analysis based on regression charts identifying key trends and patterns affecting equity in learning. Our findings show that students enrolled in private schools had better access to online education in both cities. The study also revealed the significance of cultural inclusivity in online learning. The diversity of students’ cultural backgrounds affects the process and outcomes of online learning. The findings from this research can serve as valuable guidance to enhance pedagogical designs that adapt better to online learning practices for school students during the COVID-19 pandemic or any future unexpected crises. We provide recommendations for policymakers and educators to promote inclusivity in online education.